Analisis Pengaruh Kualitas Pelayan Dan Promosi Terhadap Loyalitas Nasabah Melalui Kepuasan Nasabah Sebagai Variabel Intervening: Studi Kasus PT Pegadaian Kantor Cabang Tebing Tinggi - Lubis, Nanda Sri Dewi; Gunawan, Didik (Sekolah Tinggi Ilmu Ekonomi Bina Karya, 2023)
This study aims to find out more clearly how the Analysis of Service Quality and Promotion of Customer Loyalty through Customer Satisfaction as an Intervening variable (Case Study of PT Pegadaian Tebing Tinggi Branch Office). This study uses quantitative methods. This type of research is explanatory research which explains the causal relationship between variables and hypothesis testing. The sample used in this study amounted to 100 respondents with the accidental sampling method with the characteristics of customers who have made purchases and used the services of PT Pegadaian Tebing Tinggi Branch. Data analysis in this study used Validity Test, Reliability Test, Hypothesis Testing (t test). The data processing program in this study uses a software program Smart PLS version 3.0. The results of the study indicate that Service Quality has an effect on Customer Satisfaction of PT. Pegadaian Tebing Tinggi Branch. Promotion has an effect on Customer Satisfaction of PT. Pegadaian Tebing Tinggi Branch. Service Quality has no effect on Customer Loyalty of PT. Pegadaian Tebing Tinggi Branch. Promotion has no effect on Customer Loyalty of PT. Pegadaian Tebing Tinggi Branch. Customer Satisfaction has no effect on Customer Loyalty of PT. Pegadaian Tebing Tinggi Branch. Service quality has no effect on Customer Loyalty through customer satisfaction as an intervening variable on the product of PT Pegadaian Branch Tebing Tinggi. Promotion has no effect on Customer Loyalty through Customer Satisfaction as an intervening variable on the product of PT Pegadaian Branch Tebing Tinggi